Cartografias com crianças: composições e paisagens que afirmam o desejo de uma vida bonita - Medeiros, Fernanda Vieira de (2012)
Even when everything asks for a little bit more calmness. Until the body asks for a little bit more soul. Life does not stop... While time speeds up and asks for a hurry, I refuse, linger over, waltz off, life is so rare… As a chant to Patience by Lenine, to the details, to the unnoticed, to what produces difference, we write with other arrangements, other rhythms, other subtle compositions, verses of a researchmelody. Possible crossings at meetings, conversations, experiences as an art of accompanying some deterritorialized rhizomatic movements. A web-writing, a cartography hanking. Lines which come and go, they leap, dance and hide to the zest of willings, of performances within each plateau. Research spinned with Deleuze’s and many other’s thoughts… Translocations caused by a flight “Plunct Plact Zum”: Trips by a Mad Stamper, strength-music, touchstone of an adventure problematizing which produced itself among children’s hushing around and adults’ steps. An agency-music, ticket to new ideas on the production lines themselves. Desire-thought of cartographies of children’s territory which agencied itself through preschool meanders. Beautiful life of a chant: Where do you think you are going? We strolled across a geography, space of “midst”, sky and sea meeting, flew-rowed. Worlds` creation. Thinking art. We slipped on molar and molecular soil, digged some lines of escape lapidating gems of chronological time and polishing images of experience which outbreak the look, the smile, the hug and the children`s inventions. Through stones and ruins, valleys and mountains, ideas waterfalls, clear and dark sky, clouds and thunders, noises and chants, we drew with question-conversations a way of living, of thinking, of human self making, excessively human. A beautiful life within compositions and landscapes… Stuttering writing… possible others. Is it art? That is the question